Ações afirmativas : cotas para negros nas universidades públicas - Britto, Thays Oliveira de (2011)
Brazil was the country for longer maintained the system of slavery, received a huge amount of blacks that were sold as a commodi ty to work on large farms. The abolition only occurred in 1888, the slave felt free in complete state of disrepair and became associated with a delay situation for the country. Several years elapsed after the end of slavery, racism and prejudice becomes the main justification for the existence of economic inequality of blacks compared to whites. By arguments seeking to justify inequality by prejudice, has developed several social policies in order to socially include the black and give them a better quality of life. One of these social policies are the affirmative actions for education, which aims to insert blacks in higher education through the university quota. It happened that the educational inequality in Brazil can be explained by several factors, one being the low quality of public education provided by the state that leads to unequal opportunities.It is known that education is a major factor for the development of the country, capable of providing equal opportunities and improving human development. Education has a power to liberate the individual as it provides knowledge, political participation, changes in values and ability to rise socially. This study aimed to identify what the true cause of educational inequality between blacks and whites and the prejudice that still exists in the country is able to prevent social rise of the black, through bibliographic research and statistical survey of official bodies such as the IBGE Brazilian Institute of Geography and Statistics that analyzed the numbers of social exclusion in the country. The results and discussions show that despite racism being considered a crime in the Federal Constitution, is still present in Brazilian society, but this factor is not an element capable of preventing the rise of black social, economic factors are the real causes of inequality, so as the lack of quality education and poverty. This study highlights the need to develop public policy where people are more benefits underfunded. It concluded with the suggestion to change the racial quotas and affirmative action that social policies must go hand in hand with policies to combat poverty and social inequality